Quantification of CD8+CD38+ T lymphocytes by flow cytometry does not represent a good biomarker to monitor the reactivation of cytomegalovirus infection after allogeneic hematopoietic stem cell transplantation - Lino,Vânia Abadia Soares (2011)
BACKGROUND: Infection/reactivation of cytomegalovirus is a major cause of morbidity and mortality in immunocompromised transplant patients. It has already been observed in kidney and liver transplantation patients that cytomegalovirus disease is accompanied by significant increases in circulating CD8+CD38+ T lymphocytes. There are no reports that study CD8+CD38+ T lymphocytes to monitor/diagnose cytomegalovirus disease in hematopoietic stem cell transplantation patients. OBJECTIVE: The aim of this study was to evaluate some cellular activation markers on circulating mononuclear cells (CD38 and HLA-DR) in patients submitted to hematopoietic stem cell transplantation and to establish any correlation with cytomegalovirus disease as diagnosed by antigenemia. METHODS: Blood samples of 15 transplant patients were analyzed by flow cytometry using anti-CD3, anti-CD4, anti-CD8, anti-CD38, CD16, CD56 and anti-HLA-DR monoclonal antibodies and the results were evaluated in respect to cytomegalovirus antigenemia measured by indirect immunofluorescence. Minitab for Windows was used for statistical analysis and a p-value < 0.05 was considered significant. RESULTS: Patients with positive antigenemia did not show any significant increase in the percentages of cells expressing the CD38 or HLADR activation markers when compared to patients with negative antigenemia. On the contrary, all patients showed high percentages of these cells independent of the presence of cytomegalovirus disease. CONCLUSIONS: This study suggests that the investigation of these lymphocyte sub-populations in patients submitted to hematopoietic stem cell transplantation does not seem to contribute to the early identification of cytomegalovirus disease.